(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Blood flow intensity plays an important role in the recovery after exercising. Research aim was to compare the effect of passive rest and passive foot movement on calf muscle blood flow applying dosed static physical loads. Research methods. Eighteen adult males were divided into two sub-groups. Participants of the study performed two isometric 30-s workouts at 75% of MVC with 20 minutes interval for the recovery between the workouts. During the first stage one sub-group performed workout and a passive recovery was applied while the subjects of the second sub-group performed passive foot flexion movements. During the second stage the form of recovery was changed. Arterial blood flow intensity was registered during venous occlusion plethysmography and passive foot flexion movements were performed by special mechanical equipment. Research results. The results obtained during the study showed that maximal increase of blood flow registered at 21 second after the workout was (52.0 ± 2.9 ml/min/100 ml), while the application of passive movements before the workout decreased the blood flow intensity (45.0 ± 2.6 ml/min/100 ml). It was significantly (p < 0.05) lower compared to passive rest. Discussion and conclusions. These effects can be explained by reduced venous filling and increased venous vascular reserve capacity in the calves. The results obtained during this research allow concluding that passive foot flexion manoeuvre applied before the isometric workload faster decreases the blood flow intensity during the recovery. Keywords: arterial blood ﬂow recovery, isometric physical workout, passive foot movement, passive rest.